Clinical Severeity of Covid-19 Affected by Thyroid Disease - Syed Ali Haziq Bukhari, Awais Ghulam Nabi, Muhammad Irfan Farooqi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The current study’s goal is to determine if thyroid disease can predict the severity of COVID-19. Study Design: Prospective Study Place and Duration: THQ kotmomin district Sargodha, Punjab Medical College. March 2021-SEP 2021 Methods: This research included 122 patients of both sexes. Patients ranged in age from 20 to 75. In order to obtain demographic data, all patients completed a permission form in which they said that they were willing to have this information used for research purposes. A PCR test was performed on each patient to establish the presence of a pandemic illness. Two equal groups, I and II, were created for the patients. Patients with symptoms in group I comprised of 61 patients, while group II had 61 patients without symptoms. Thyroid-stimulating hormone (TSH), thyroid peroxidase antibody (TPA), thyroid free triiodothyronine (FT3), and thyroglobulin antibody were all tested for in the participants’ blood (TGA). SPSS 24.0 edition was used for the whole data set to be analysed. Results: There was no any significant difference of age and BMI among both groups. Majority of the patients among both groups 40 (65.6%) and 39 (63.9%) were males. 35 (55.7%) of the patients in group I had severe disease, whereas 20 (32.8%) of those in group II had severe infection. Group I patients exhibited significantly lower levels of free thyroxine (FT4) and free triiodothyronine in their blood than the rest of the patients (FT3). The levels of IL-6 in group I were significantly greater than in group II. Among the 10 (16.4%) people in group I, had an overt thyroid problem, compared to 5 (8.2 % in group II . 17 (27.9%) instances of thyroid nodules larger than 1cm were detected in group I, whereas 6 (9.8%) cases of nodules larger than 1cm were found in group II. Group I had a considerably higher mortality rate, as shown by a p value of 0.05. Conclusion: Thyroid hormone abnormalities were more common in very sick COVID19 patients studied in this investigation. COVID19 patients’ FT3 levels at the time of hospital admission may serve as a prognostic indication. Nodules on the thyroid may be a symptom of a severe form of COVID-19.